Chronic bronchitis and urban air pollution in an international study. Issue 12 (17th July 2006) - Sunyer, J; Jarvis, D; Gotschi, T; Garcia-Esteban, R; Jacquemin, B; Aguilera, I; Ackerman, U; de Marco, R; Forsberg, B; Gislason, T; Heinrich, J; Norbäck, D; et al.
Abstract : Objectives: The chronic effects of urban air pollution are not well known. The authors' aim was to investigate the association between the prevalence and new onset of chronic bronchitis and urban air pollution. Methods: Subjects from the general population randomly selected for the European Community Respiratory Health Survey (ECRHS I) during 1991–93 in 21 centres in 10 countries were followed up from the years 2000 to 2002 (n = 3232 males and 3592 females; average response rate = 65.3%). PM2.5 and elements, with the same equipment at centre level, and home outdoor NO2 in 1634 individuals were measured. Hierarchical models were used. Results: The prevalence and new onset of chronic phlegm during follow up were 6.9% and 4.5%, respectively, 5.3% in males and 3.5% in females. Smoking, rhinitis, poor education, and low social class were associated with (prevalence and new onset of) chronic phlegm in both genders, and occupational exposures in males and traffic intensity (adjusted odds ratio for constant traffic, OR = 1.86; 95% CI 1.24 to 2.77) as well as home outdoor NO2 (OR > 50 μg/m 3 v < 20μg 3  =  2.71; 95% CI 1.03 to 7.16) among females. PM2.5 and S content at centre level did not show any association with prevalence or new onset of chronic phlegm. Similar results were obtained with chronic productive cough. Conclusion: Individual markers of traffic at household level such as reported intensity and outdoor NO2 were risk factors for chronic bronchitis among females.